Sense-ational organization theory! Practices of democratic scriptology. Issue 1 (February 2019) - Rhodes, Carl
This article critically reviews the use of non-conventional writing in organization studies from the 1980s to the present day as it relates to the relationship between freedom, politics and theory. Just as research justifies itself through an elaboration of methodology, it is suggested that we can consider 'scriptology' – the reflexively aware articulation of the relationship between writing and knowledge – as a means to liberate knowledge production in organization studies from its self-imposed conservatism. While there are numerous actual examples of non-conventional scriptologies in use, it is argued the most politically radical and emancipatory of them can be found in contemporary feminine and feminist writing. Such writing provides a new textual aesthetic for organization studies that promises a democratic and egalitarian practice where expression seeks to defy the rules that would inhibit it rather than adhere to the ones that would authorize it. Such scriptologies can provide a way that knowledge can try, in its way, to be free.